A REVIEW ON DRUGS USED FOR SHWETA PRADARA (LEUCORRHOEA) IN AYURVEDA : Array - Pandey, Prachi (Ayurline: International Journal of Research in Indian Medicine, 2022)
Reproductive tract infection is one of the major problems which women deals in their lifecycle. This problem is vital issue in developing countries due to negligence and unawareness regarding RTI. Women are not aware about severity of their own health problems and are reluctant to seek medical help for the same. Shweta Pradara i.e. Leucorrhoea is not a disease but a symptom of various disease which further leads to major health issues in women. In Ayurveda all gynecological problems are collectively described under yonivyapada. In Brihatrayee i.e. Charak Samhita, Shushrut Samhita, Astaangsangraha and Astaanghridaya did not used the term Shweta Pradara to described white vaginal discharge instead they used Shweta Strava. But later in Sharangdhara Samhita, Bhavaprakash Samhita and Yogaratnakar Shweta Pradara has been described. In Ayurveda many drugs had been described for the treatment of Shweta Pradara.